Functional Behavior Assessment Practices Used by Canadian Behavioral Health Practitioners. Issue 2 (8th January 2020) - Saini, Valdeep; Cox, Alison
Abstract: A proportion of children and adults in Canada are identified as having an intellectual or developmental disability (I/DD). Moreover, the prevalence of autism spectrum disorder (ASD) in Canadian children has increased substantially over the past decade. Research has shown that these populations have a greater likelihood to engage in severe destructive behavior such as self‐injury and aggression, which places them at risk for exposure to intrusive interventions and denial of services. Functional behavior assessment (FBA) is an assessment strategy that takes the environmental variables responsible for the development and maintenance of destructive behavior into consideration and has shown to be the most informative for developing effective treatments for destructive behavior. We conducted a nation‐wide survey that queried behavior‐analyst practitioners working in the I/DD and ASD service sectors about their beliefs and use of FBA in clinical practice. We compared the results of this survey with similar surveys conducted in the United States. The results indicated that most Canadian practitioners are conducting some type of FBA; however, many of these assessments are not comprehensive and missing important components of the assessment process. We discuss the implications of these findings, as well as the barriers to implementing FBA in practice.